The Authentic Materials for Teaching English to Young Learners: Teachers’ Perception - Dian Erlina; Winda Retno; Muhamad Holandyah; Lenny Marzulina; Herizal Herizal (Edukasi, 2023)
This qualitative research aimed to find out the teachers' perception toward the use of authentic materials in teaching English to young learners at the Islamic elementary schools in Palembang, South Sumatra, Indonesia. The participants of this research were English teachers from several Islamic elementary schools in Palembang. They were selected through the implementation of a purposeful sampling technique. The research data were obtained through one-on-one interviews with open-ended questions. This research utilized thematic analysis procedures to analyze the interview data and member checking to validate the accuracy of the findings. The results indicated that the teachers had a positive perception toward the use of authentic materials in their English classroom activities and tasks. Using authentic materials helped improve the students’ language ability and their enthusiasm for learning English. However, the teachers still faced several difficulties in selecting the appropriate existing authentic materials for their students. It implied that teachers need to make some adaptations to using existing authentic materials to attain greater appropriateness from the materials to suit their students’ specific needs and characteristics to facilitate effective English learning.